2013
DOI: 10.1371/journal.pone.0083754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin II Type 2 Receptor Overexpression on the Growth of Hepatocellular Carcinoma Cells In Vitro and In Vivo

Abstract: Increasing evidence suggests that the renin-angiotensin system (RAS) plays an important role in tumorigenesis. The interaction between Angiotensin II (AngII) and angiotensin type 1 receptor (AT1R) may have a pivotal role in hepatocellular carcinoma (HCC) and therefore, AT1R blocker and angiotensin I-converting enzyme (ACE) inhibitors may have therapeutic potential in the treatment of hepatic cancer. Although the involvement of AT1R has been well explored, the role of the angiotensin II Type 2 receptor (AT2R) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 46 publications
(57 reference statements)
4
30
0
Order By: Relevance
“…Firstly, our present results revealed increased expression of AT1 and decreased expression of AT2 in HCC cells and tissues by RT-PCR, Western Blot and IHC analysis, which is consistent with previous studies [36,46]. Next, blocking AT1 and AT1 siRNA significantly inhibited Ang II-induced cell proliferation and inflammatory responses in HCC cell lines, thus we could draw the conclusion that Ang II might be an important factor in proliferation and inflammation of HCC via the activation of AT1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Firstly, our present results revealed increased expression of AT1 and decreased expression of AT2 in HCC cells and tissues by RT-PCR, Western Blot and IHC analysis, which is consistent with previous studies [36,46]. Next, blocking AT1 and AT1 siRNA significantly inhibited Ang II-induced cell proliferation and inflammatory responses in HCC cell lines, thus we could draw the conclusion that Ang II might be an important factor in proliferation and inflammation of HCC via the activation of AT1.…”
Section: Discussionsupporting
confidence: 92%
“…Ang II, the key effector in the RAS, acts through two well-defined receptors: AT1 and AT2 [35,36]. Recent study reported that AT1 expression was associated with enhance angiogenesis and cellular proliferation rate, but no relationship was found with AT2 in breast cancer [8].…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer cells, AT 2 R overexpression induced apoptosis independently of Ang II but depended on p38-MAPK, caspase 3 and caspase 8 and was mediated via an extrinsic cell death-signaling pathway that partially depended on P53 activation (29). Consistent with this, AT 2 R overexpression in hepatocellular carcinoma cells also induced apoptosis, which was associated with a significant increase in caspase 3 activity and p38 phosphorylation (25). As noted above, Ang-(1-7) might promote tumor cell apoptosis by disrupting the stoichiometry of the AT 1 R and AT 2 R and subsequently altering their signaling.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, PI3K/Akt signaling and epithelial growth factor receptor transactivation are involved in the regulation of AT 1 R-induced tumor cell proliferation (23,24). AT 2 R counteracts the effects of AT 1 R and exerts antiproliferative action by reducing S-phase cells and increasing G1-phase cells via suppression of CDK4 and cyclinD1 expression (25). AT 2 R also stimulates the activity of phosphotyrosine phosphatases (PTPs), which have been implicated in cell growth and differentiation (26).…”
Section: Discussionmentioning
confidence: 99%
“…The apparent superiority of sartans over ACE I may be due to the selective inhibition of angiotensin II receptor 1, responsible of the pro-fibrogenic and pro-angiogenic activity of angiotensin, while pro-apoptotic and anti-tumorigenic activity of receptor 2 is preserved and even enhanced in patients administered sartans unlike ACE I which prevent the binding of angiotensin II to both receptors[37]. However, these preliminary results still need further confirmation.…”
Section: Prevention Of Recurrence After Rfamentioning
confidence: 99%